LANGUAGE CHOICE IN TEACHING CONTENT SUBJECTS AT ENGLISH DEPARTMENT FKIP UNIVERSITY OF MATARAM - Erssa Renanda; Muhammad Amin; Ahmad Zamzam (Program Studi Pendidikan Bahasa Inggris, 2021)
This research discusses the language choice in teaching content subjects used by lecturers in the online classroom. It aims at finding out the types of code-switching and code-mixing and the reason for using both of them. This study is a descriptive qualitative. The researchers observed and collected the data by attending the online class. The researchers recorded the conversation from the start until the end of the class. After gaining the data, the researchers transcribed them into written data and then classified them based on the types of code switching and code mixing. They then analyzed the reasons why code-switching and code-mixing were used. The result of the data analysis showed that the most frequently used type of code-mixing was Intra-Sentential, while the most applied type of code-switching was extra-sentential. In addition, the most dominant reason is the intention of clarifying the content of the course for the interlocutor.